Biventricular assessment of light-chain amyloidosis using 3D speckle tracking echocardiography: Differentiation from other forms of myocardial hypertrophy. (15th November 2018) - Vitarelli, Antonio; Lai, Silvia; Petrucci, Maria Teresa; Gaudio, Carlo; Capotosto, Lidia; Mangieri, Enrico; Ricci, Serafino; Germanò, Giuseppe; De Sio, Simone; Truscelli, Giovanni; Vozella, Federico; Pergolini, Mario Sergio; et al.
Abstract: Background: Given that in patients with cardiac amyloidosis (CA), deposition of amyloid protein is not restricted to the left ventricular (LV) myocardium, it can be hypothesized that the diagnostic value of deformation mechanics would be enhanced by considering right ventricular (RV) strain measures. The aim of the present study was to examine the potential utility of left ventricular (LV) and right ventricular (RV) deformation and rotational parameters derived from three-dimensional speckle-tracking echocardiograph (3DSTE) to diagnose cardiac amyloidosis and differentiate this disease from other forms of myocardial hypertrophy. Methods: Twenty-three patients with biopsy-proven light-chain (AL) amyloidosis, 23 patients with systemic arterial hypertension (HTN), 23 patients with hypertrophic cardiomyopathy (HCM), 23 athletes and 23 normal controls were prospectively studied by conventional echocardiography and 3DSTE. LV longitudinal strain (LV LS), LV circumferential strain (LV CS), RV global longitudinal strain and RV free-wall longitudinal strain (RV FW LS) were obtained by 3DSTE, as well as LV rotation and rotational velocities. Results: LV and RV longitudinal strains were reduced in cardiac amyloidosis (CA) patients compared to controls. By multivariate analysis, LV basal LS ( p = 0.002), LV peak basal rotation ( p = 0.003), and RV basal FW LS ( p = 0.014) were independently associated with CA in the overall population. A significant improvement in global χ 2 value was noted with RV 3D-strain parameters over only LV-3DSTE + conventional indices for detection of CA ( p < 0.001). Comparison of ROC curves showed that the AUC using combined LV basal LS, LV basal rotation and RV basal FW LS had a higher discriminative value than the other echocardiographic parameters used for detecting CA (AUC 0.93, 95%CI 0.81–0.97). Conclusions: Three-dimensional speckle tracking echocardiography reveals regional and global biventricular dysfunction in CA. Assessment of RV ventricular dysfunction has an additive value in differentiating CA from other causes of myocardial wall thickening. Highlights: We examined the potential utility of three-dimensional speckle-tracking echocardiography in cardiac amyloidosis (CA). Three-dimensional speckle tracking echocardiography revealed regional and global biventricular dysfunction in CA. Right ventricular dysfunction assessment had an additive value in differentiating CA from other myocardial hypertrophies.